Clinical case of toxocariasis chorioretinitis - I. G. Pikhovskaia; N. V. Savchenko; A. L. Zhirov; S. V. Tonkonogii (Oftalʹmologiâ)
The clinical case of a toxocariasis chorioretinitis which is of interest for ophthalmologists is described. Insufficient knowledge of clinic and diagnostics of a lesion of eyes by Toxocara canis, their infrequent occurrence, similarity of the ophthalmologic picture with inflammatory diseases and eye neoplasms can be at the bottom of gross diagnostic mistake and wrong choice of treatment tactics.